Influence of Different Offset Angles of Inlet Guide Vanes on Flow Characteristics of Centrifugal Pump - Lin, Peifeng; Yang, Tao; Xu, Wenbin; Zhu, Zuchao (Frontiers in Energy Research, 2022)
The efficiency of the impeller machinery can be improved by the inlet guide vanes has been widely recognized, but the relationship between the external characteristics of the centrifugal pump and the internal flow state needs further study. In this paper, the flow characteristics of the centrifugal pump with different offset angles of inlet guide vanes (IGVs) are simulated based on the SST k-ω turbulence model. The influence of the offset angle of the IGV on the internal flow and energy dissipation of the centrifugal pump is analyzed by using the entropy generation theory and Q-criterion. The research results show that the increase of the offset angle is beneficial to reduce the intensity of vortex in the volute and impeller, while the energy loss is reduced by 21.12% and 17.82% at 0.6Qd and 0.8Qd, respectively. However, excessive offset angle of the IGV tends to cause greater energy loss in the inlet pipe, thus reducing the head and efficiency of the centrifugal pump. In terms of external characteristics, the pump with 25° IGVs has the best head and efficiency improvement. Under three small operating points, the pump with 25° IGVs increased the head by 2.11%, 0.95% and 0.73%, and the efficiency increased by 2.51%, 1.67% and 1.25%, respectively, compared with 0° IGVs. The research in this paper contributes to the performance improvement of centrifugal pumps operating at low flow conditions.